NAMAARI POWER IN RAYA AND THE LAST DRAGON MOVIE: MULTIMODAL DISCOURSE ANALYSIS - Purwanto, Atmi Maharani; Kurniawan, Muhammad Hafiz (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2024)
Raya and the Last Dragon is a popular animated film from Walt Disney Animation Studios, featuring an antagonist named Namaari. This study aims to examine the interactive meaning of a particular scene and determine the representation of power by Namaari as the female antagonist character during the orientation stage, specifically from minute 0:11:54 to 0:16:37. To identify the representation of Namaari in the movie, a combination of verbal and non-verbal modes is analyzed. This research employs a descriptive qualitative method, utilizing Kress and van Leeuwen’s visual grammar theory to investigate movement, Baldry and Thibault’s approach to analyze the macrophase, and Halliday’s textual metafunction to examine the verbal mode. Additionally, Sutherland's power model, incorporating Allen’s conception of power, is used for a deeper analysis of female power. The study reveals that Namaari embodies different types of power as a female antagonist, such as power-over, power-to, and power-with, based on the frameworks of Sutherland and Feltey. Besides adapting masculine traits, Namaari demonstrates her power through verbal clauses, detachment, and equality angles. These features portray Namaari as an equal to Raya, both verbally and visually. Namaari tends to convey information through declarative clauses, adopting a friendly demeanor (using positive face strategies) to deceive Raya and gain access to the Dragon Gem.